ZAKAT SEBAGAI PENGURANG PAJAK PENGHASILAN PADA BADAN AMIL ZAKAT - Sri Andriani; Fitha Fathya (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2013)
Tax is become the highest acceptance for a country. There is no one country in the world get higher acceptance sector than tax. Because of its high proportion for a country, the tax acceptance is struggled by the government. In case, tax is so important for a country acceptance, then the society awareness came along for the importance of zakat too. Both of tax and zakat need a right management. Bad management of both will make productions contradictive for the building of the nation. One of them is a double load to pay tax and zakat. Goal of this research is to analyze the effectiveness management of zakat as subtrahend of tax in BadanAmil Zakat (BAZ), East Java. This research using descriptive qualitative approach and will describe systematically about the research focus (zakat as subtrahend of tax). Data analysis is done to simplify the data, so that the data will be easy to read and interpreted. The data collection is done by observation, interview, and documentation. Data analysis by three phases : data reduction, data presentation, and verification. From this research, BAZ in East Java shows that zakat as subtrahend of tax has a big impact for the potential tax acceptance. Then, it can be concluded that realization of the law of zakat and tax must be increased.